2023
DOI: 10.1021/acsabm.2c00666
|View full text |Cite
|
Sign up to set email alerts
|

Silk Nanocarrier with Tunable Size to Improve Transdermal Capacity for Hydrophilic and Hydrophobic Drugs

Abstract: Transdermal drug delivery is an attractive option for multiple disease therapies as it reduces adverse reactions and improves patient compliance. Water-dispersible β-sheet rich silk nanofiber carriers have hydrophobic properties that benefit transdermal delivery but still show inferior transdermal capacities. Thus, hydrophobic silk nanofibers were fabricated to fine-tune their size and endow them with desirable transdermal delivery capacities. Silk nanocarrier length was shortened from 2000 nm to approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Silk nanofiber size was gradually reduced from 2000 to <100 nm and investigated for their capacity to permeate through the skin. Particles were fabricated first using a concentration-dilution protocol [ 132 ], where SF solution was concentrated while being heated over the course of 24 h to form particles, then diluted and heated until a gel was formed. An ultrasonic treatment was then employed between 100–650 W for 5–30 min to prepare silk nanoparticles of different sizes by altering the ultrasonic intensity and time.…”
Section: Particulate Drug Delivery Systems In Wound and Skin Regenera...mentioning
confidence: 99%
“…Silk nanofiber size was gradually reduced from 2000 to <100 nm and investigated for their capacity to permeate through the skin. Particles were fabricated first using a concentration-dilution protocol [ 132 ], where SF solution was concentrated while being heated over the course of 24 h to form particles, then diluted and heated until a gel was formed. An ultrasonic treatment was then employed between 100–650 W for 5–30 min to prepare silk nanoparticles of different sizes by altering the ultrasonic intensity and time.…”
Section: Particulate Drug Delivery Systems In Wound and Skin Regenera...mentioning
confidence: 99%
“…Reproduced with permission. [71] Copyright 2023, American Chemical Society. diclofenac, and vitamin B12 drugs based on chitosan and phospholipid nanofibers (Figure 10).…”
Section: Nanofibers Based On Natural Polymersmentioning
confidence: 99%
“…It was found that improved transdermal capacity was achieved for smaller size carriers ( Figure ). [ 71 ] Similarly, in comparing the NPTDD efficiency of different sizes of curcumin nanocrystals mediated by HA MN, Miao et al. found that smaller particle sizes were more conducive to their entry into the deeper layers of the skin.…”
Section: Forms and Mechanism Of Nptdd Systems In Assisted Drug Transd...mentioning
confidence: 99%
“…The BSNs have been used to load hydrophobic and hydrophilic drugs and ingredients to achieve different bioactivity such as angiogenic property and anti-inflammatory capacity. [58][59][60] The drug-loaded BSNs were also treated with electrical fields to develop bioactive hydrogels with anisotropic structures for nerve regeneration. [21] It is possible to load anticoagulant molecules such as heparin and aspirin on the BSNs and then prepare the vascular grafts with anticoagulant capacity through the same fabrication strategy.…”
Section: Vascular Regeneration With the Composite Grafts In Vivomentioning
confidence: 99%